(untitled) (Argos, 2025)
The purpose of this paper is the study of the treatment offered in Quintilian’s Institutio Oratoria, in the artes of Donatus, Diomedes and Consentius, and in Pompeius’s commentary on the work of Donatus, of the standard examples regarding the use of pluralia tantum in singular: scala, scopa, quadriga. The analysis of the ambiguity of the pluralia and singularia tantum gains relevance as it transcends the mere automated discussion of a commonplace of the artes grammaticales, becoming a problem of linguistic description, when the issue of its coherence for the description of the entire language is raised.